Anatomical evaluation of the craniometric points and dimensions among adult's populations of the South-Eastern Nigerians and its implication for intracranial surgical procedures - David Lekpa Kingdom; Vidona Willy Barinem (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2021)
Background: The understanding of Craniometry with its associated craniometric points and dimensions have found immense applicable relevance in anthropology and neuroscience, ranging from growth determination, estimation of cranial deformities, personal biological profile identification and facial reconstructive surgeries, analysis of evolution of the human species in archeology as well as age variations.  Objective: The aim of this study was to evaluate the craniometric dimensions among adults' subjects in Eastern Nigerian State.  Methods: Research data was collected from Computed Tomography scans in the Radiological Department of Federal Medical Centre, Umuahia, Nigeria with strict adherence to inclusive and exclusive factors. A total number of 150 human CT scans were used in the findings. Craniometric parameters were calculated - derived from the two and three coordinate points for linear and angular measurements respectively.  Results: Results revealed that age group 36-45 had the lowest cranial parameters and age group 56-65 had the highest cranial parameters.  Conclusion: It was concluded that cranial parameters does not increase as age increases throughout life. The study findings will be useful to the anatomists, anthropologists and neuroscientists.